An observational study of clinical presentation and emergency surgical management of obstructed inguinal hernia repair - Godhani, Parag H.; Modi, Jenish V. (International Surgery Journal, 2024)
Background: Inguinal hernias, one of the most causes of surgical admissions and referral of patients from primary physicians. Hernia is defined as protrusion of whole or a part of viscus through the wall that contains it. Strangulated hernia (irreducibility+obstruction+arrest of blood supply) is defined as a hernia in which blood supply of herniated viscus is constricted so much by swelling and congestion that it causes the arrest of its circulation. Methods: The study carried out in 50 patients between August 2019 to December 2022 including patients having obstructed inguinal hernia presenting as emergencies/irreducible. Patients with obstructed hernia required emergency exploration through inguinal incision where on the basis of intraoperative presence of toxic fluid, mesh placement was decided. Results: Total 50 patients were studied with the highest incidence at age 61-75, the most common site of obstruction was internal inguinal ring (n=42), most commonly presenting with symptoms of pain (n=50), swelling (n=50) followed by vomiting (n=29). Conclusions: The right sided hernia was more commonly involved in obstruction at the level of the internal inguinal ring followed by superficial ring and mesh was kept according to the presence of toxic fluid. The most common procedure was posterior wall repair (n=31) with or without resection and anastomosis followed by meshplasty (n=19) where the complication were less observed with meshplasty (n=3) and highest complication were observed in posterior wall repair (n=9) with or without resection and anastomosis.